2016
DOI: 10.17116/terarkh201688715-24
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ph-negative lymphoblastic leukemias in adults: Risk factors in the use of the ALL-2009 protocol

Abstract: A lower chemotherapeutic load and a small number of allogeneic BMTs did not affect total positive treatment results in adult patients with ALL, by complying with the principle achieving the continuity of cytostatic effects and by preserving the total cytostatic loading dose. The results of the Russian investigation casts some doubt on the necessity of using very intensive consolidation cycles and performing a large number of allogeneic BMTs in adult patients with ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
1
0
3
Order By: Relevance
“…In that case, an important prognostic factor is age; event-free survival of children in various age groups varies from 83–97% (1–5 years) to 49–66% (10–15 years). Recently, the Russian Research Group for the Treatment of Acute Lymphoblastic Leukemia (RALL) has demonstrated that the 5-year relapse-free survival rate in adult patients under 30 years of age is 71.5%, while this indicator in patients aged 30–55 years is lower – 61.8% [ 2 ]. Adults and children with ALL have been demonstrated to differ not only in the survival rate, but also in the biological properties and prognosis of the disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that case, an important prognostic factor is age; event-free survival of children in various age groups varies from 83–97% (1–5 years) to 49–66% (10–15 years). Recently, the Russian Research Group for the Treatment of Acute Lymphoblastic Leukemia (RALL) has demonstrated that the 5-year relapse-free survival rate in adult patients under 30 years of age is 71.5%, while this indicator in patients aged 30–55 years is lower – 61.8% [ 2 ]. Adults and children with ALL have been demonstrated to differ not only in the survival rate, but also in the biological properties and prognosis of the disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…В федеральных центрах ОВ и БРВ составили 73 и 71 %, а в региональных -52 и 56 % соответственно (р < 0,0001; р = 0,0009) (рис. 3,4).…”
Section: материалы и методыunclassified
“…При Т-ОЛЛ ни для каких из выбранных цитогенетических маркеров не удалось подтвердить их про- Оба протокола основаны на принципе низкодозного, но постоянного длительного воздействия с незначительной долей алло-ТГСК [3,6]. Большинство исследовательских групп в настоящее время используют так называемый «педиатрический» подход, подразумевая под этим применение курсов высокодозной многокомпонентной консолидации с метотрексатом, цитарабином в высоких дозах, интеграцией пегилированной аспарагиназы.…”
Section: материалы и методыunclassified
See 1 more Smart Citation